German residential tourists and residents in Southern Spain (Andalusia). Distribution and recent evolution - Cantarero-Prados, Francisco José; Nieto Figueras, Cristina; Sickert, Jacqueline (Springer, 2022)
On the basis of an approach to the state of the matter regarding the residential tourism segment, this paper takes a descriptive approach to German residential tourism in the Spanish region of Andalusia based on census registration, an administrative act used by a large number of foreigners in eminently touristy territories when they strengthen their relations with the destination.The identification of specific patterns and dynamics that distinguish the German colony from other nationalities in specific areas of the region, suggest future lines of research into the origin, nature and territorial implications of the decisions taken by this contingent
Keywords: Alemanes - España meridional; Viajeros alemanes - España meridional; Turismo residencial; Empadronados extranjeros; Andalucía; Turismo; Alemanes